Making it work: A case study of an elite athlete navigating her way through pregnancy and return to sport postpartum - Hayman, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Historically, motherhood signalled the end of an elite athlete's career. However, we are now witnessing a shift away from motherhood and being an athlete as two mutually exclusive periods in time, to an increasing number of elite female athletes wanting motherhood to be a part of their athletic journey. Although the exact numbers of elite female athletes who become pregnant and return to sport postpartum is not known, research suggests pregnancy and childbirth within high-performance sport is an increasing phenomenon with more athletes choosing to continue their training during pregnancy and return to sport and competition postpartum. Despite this phenomenon, there remains a paucity of literature examining the exercise behaviours of elite athletes during pregnancy, and the maternal and foetal outcomes of athletes who exceed exercise during pregnancy recommendations. Of the literature that does exist, much of the data has been subjectively collected via qualitative approaches. Only two studies to date provide quantitative insight into the training and exercise characteristics of elite athletes during pregnancy, one that involved a sherpa and the other a cross-country skier, both of which adopted a longitudinal observational methodological approach. Longitudinal observational case studies represent a practical and ethically defensible manner to examine the exercise behaviours among elite athletes during pregnancy, particularly in women who are already active and intend to remain highly active during pregnancy. As such, Associate Professor Melanie Hayman will present novel data from an ongoing case study of a sprint kayaker navigating her way through pregnancy and return to sport postpartum as an elite athlete.